The forgiven - Perry, Marta (New York : Berkley Books, 2014)
When three women, all cousins, are given the task of sorting through the treasures of several generations of their Amish family, they each discover a story from the past that provides insights and inspiration for their own lives.
Keywords: Single women -- Fiction; Amish -- Fiction; Cousins -- Fiction; Families -- Fiction; Christian fiction